Application of concrete canvas to optimize channel construction processes (LACCEI, 2024)
The investigation that was carried out to optimize the construction system of the irrigation canals. The implementation of the concrete canvas as the main material allowed to improve the efficiency in construction time and reduce the environmental impact compared to traditional concrete. The numerical calculations and the use of specialized software allowed to obtain optimal results in the design and lining of the channel. It is interesting to note that a remarkable efficiency was achieved in an 800m2 area in just 40 days with a crew of 12 workers, which demonstrates the effectiveness of the implementation of the concrete canvas in the construction process of the irrigation canals. In summary, the results obtained in the investigation suggest that the concrete canvas is a viable system for the construction of channels, optimizing (time and cost) construction processes.